Kehidupan Pembantu Rumah Tangga di Hindia Belanda pada Pertengahan Abad ke-19 sampai Abad ke-20 - Nugroho, Andri Setyo; Nurfaizah, Dita Reista (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2020)
Historical writings mostly reveal the life of a group that is considered elite, so that the role of other groups is not so visible. As a part of colonial society life, domestic help is not widely discussed by historians. Unexpectedly, behind the work that was underestimated, domestic servants were actually one of the professions that the Dutch East Indies needed most. This article discusses the life of domestic servants in the Dutch East Indies in the mid-19th century to the 20th century. Research sources were obtained from magazines and newspapers from the mid-19th century to the 20th century, books, and journals. The results showed that the life of a domestic servant does not always get good treatment from the employer. In several cases, the tasks they performed were criticized because they were considered to have damaged the values and life order of colonial society.